PENGARUH ESG, PROFITABILITY, LEVERAGE, DAN FAKTOR LAINNYA TERHADAP FIRM VALUE - MUTIA AISYAH RAHMADINA; SILVY CHRISTINA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to provide empirical evidence regarding the influence of profitability, firm size, total asset growth, total asset turnover, leverage, liquidity, and Environment, Social, and Governance (ESG) as independent variables on firm value as the dependent variable. The population of this study consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2024. The sampling method used in this research is purposive sampling, resulting in 174 companies with a total of 522 data points that meet the predetermined sample criteria. The data analysis and hypothesis testing method employed in this study is multiple regression analysis. The results show that the profitability and leverage has an impact on firm value, as profitability indicates that firms’ ability to generate profit. On the other hand, firm size, total asset growth, liquidity, and ESG disclosure show no significant effect on firm value.